Mechanical properties of oxidized fullerene C60/epoxy nanocomposite. (2019) - Das, Subhankar; Halder, Sudipta; Islam Khan, Nazrul
Abstract: This study demonstrates the effect of pristine and oxidized fullerene dispersion on the mechanical properties of fullerene C60 -epoxy nanocomposite. Fullerene was dispersed in the epoxy system by ultrasonic mixing. Results reveal that incorporation of pristine fullerene in epoxy system enhances the tensile strength and Young's modulus by ∼13% and ∼16.5% respectively with respect to neat epoxy system, whereas oxidized fullerene enhances the same by ∼23% and ∼46%, respectively. However, the percentage elongation and toughness got reduced, whereas, the fracture toughness and strain energy release rate got enhanced by ∼101.35 % and ∼85.14 % due to the incorporation of oxidized fullerene.